Interferon-β Is Less Effective Than Other Drugs in Controlling the Rate of Retinal Ganglion Cell Loss in MS. Issue 3 (May 2021) - You, Yuyi; Barnett, Michael H.; Yiannikas, Con; Parratt, John D.E.; Matthews, Jim G.; Graham, Stuart L.; Klistorner, Alexander
Abstract : Objective: To investigate the association between disease-modifying therapies (DMTs) and the rate of progressive retinal ganglion cell (RGC) and nerve fiber loss in MS. Methods: One hundred five relapsing-remitting patients with MS were followed annually for a median of 4.0 years using optical coherence tomography. Twenty-five healthy subjects were also included as normal controls. The rates of global peripapillary retinal nerve fiber layer (pRNFL), temporal RNFL (tRNFL), and ganglion cell inner plexiform layer (GCIPL) thinning were analyzed according to DMT type using a linear mixed-effects model. Optic radiation lesion volume was measured on brain MRI and included as a covariate to minimize the effects of retrograde transsynaptic degeneration. Results: The annual rates of RNFL and GCIPL thinning were higher in patients treated with "platform" therapies (interferon-β and glatiramer acetate) compared with DMTs of higher clinical efficacy (including fingolimod, dimethyl fumarate, natalizumab, alemtuzumab, rituximab, and ocrelizumab) (difference = −0.22 μm/y, p = 0.02 for pRNFL; difference = −0.34 μm/y, p = 0.009 for tRNFL; and difference = −0.16 μm/y, p = 0.005 for GCIPL). Based on an analysis of individual treatments (interferon-β, glatiramer acetate, fingolimod, and natalizumab), interferon-β was associated with inferior RGC preservation, relative to the other drugs. No effect difference was found between glatiramer acetate, fingolimod, and natalizumab. Conclusions: Progressive loss of RGCs in patients with MS is more pronounced in patients treated with interferon-β than other DMTs. This finding may have implications for DMT selection in MS. Classification of Evidence: This study provides Class IV evidence that for patients with MS, treatment with interferon-β compared with other DMTs leads to a more pronounced rate of retinal ganglion cell loss.